Alternative substrates and containers for Ilex paraguariensis seedlings - Gabira, Mônica Moreno; Walter, Leticia Siqueira; Brito, Gabriela Scheinpflug; Schneider, Chaiane Rodrigues; Wendling, Ivar; Kratz, Dagma (Acta Iguazu, 2020)
Yerba mate is a Brazilian native species; its importance is due to cultural, environment, and economic factors. Species seedlings production needs to be improved, evaluating alternative substrates and containers. Therefore, we evaluated growth and quality of yerba mate seedlings produced on organic waste-based substrates in biodegradable and non-biodegradable containers. Commercial substrates based on pine bark (CS) and components based on sewage sludge (SS) and coal residue (granulometry from 1 to 3 mm - CR) were used. For each container, were prepared treatments with different substrate components: 75CS/25CR, 50CS/50CR, 25CS/75CR, 75CS/25SS, 50CS/50SS, 25CS/75SS, and CS. Substrates were submitted to physical and chemical analysis. The containers used were 110 cm³ polypropylene tubes, 500 cm³ polyethylene plastic bags, 460 cm³ paperpot®, and 460 cm³ TNT (non-woven fabric). Total height, stem diameter, shoot, and root dry biomass at the end of the seedlings production period were measured and total dry mass, Dickson quality index and height/diameter ratio were calculated. All containers used with commercial substrate provided satisfactory seedlings growth. The substrates showed distinct physical and chemical characteristics due to the addition of sewage sludge and coal residue, which resulted in higher pH and lower seedlings growth. Physical and chemical characteristics of substrates influenced growth and quality of yerba mate seedlings and the alternative substrates used in this study are not suitable to produce seedlings of the species on these conditions. The containers did not influence the variables used in this study.